In(ter)disciplinarity and object of study: two axes for thinking about the frontiers of art history and visual studies - López de Munain, Gorka (Eikón / Imago, 2024)
Editorial of the monograph Las fronteras de la historia del arte y los estudios visuales. Reflections on their object of study. The following contributions analyse the fluid nature of the object of study of art history, assessing the impact of the different interdisciplinary dynamics that have displaced and questioned its limits. The aim is to measure the capacity of this branch of knowledge to confront a visual culture in constant transformation, which must adapt to the emergence of new objects (such as images created with artificial intelligence) and which must permanently revise its research methodologies for the study of both contemporary works and those created in the past.